Prevalence of urinary tract infection in 2-8-week-old infants with jaundice - Partini Trihono; Arfianti Chandra Dewi; Hartono Gunardi; Hanifah Oswari (Indonesian Pediatric Society Publishing House, 2012)
Background Urinary tract infections (UTI) in infants may manifest in various ways and often appear without symptoms. Previous studies have reported that j aundice has been observed in infants aged less than 8 weeks 'With UTIs. However, a prospective study on the prevalence of UTI in infants with jaundice aged 2􀁂8 weeks is warranted in order to improve diagnosing capability and provide prompt treatment. Objective To investigate the prevalence and profiles of UTI in infants with jaundice aged 2􀁂8 weeks. Methods This cross􀁂sectional study was carried out in June-December 2011 in infants with jaundice aged 2􀁂8 weeks. Subjects were patients from the Department of Child Health, Cipto Mangunkusumo Hospital (CMS), as well as the Pediatric Polyclinics ofBudi Kemuliaan and Thamrin Hospitals. All subjects underwent total, direct and indirect bilirubin examinations, urinalyses and urine cultures. Results Of the 110 subjects recruited, the prevalence of UTI was 18.2%. More boys than girls had UTIs (13 boys, 7 girls). The microorganisms found in subjects v.ith UTIs were Escherichia coli (10/20), Klebsiella pneumoniae (8/20), and Enterobacter aerogenes (2120). Indirect hyperbilirubinemia was found in 5/20 subjects. There were more subjects with UTIs in the non􀁂exclusively breastfed (8/20) and non􀁂breastfed (8/20) groups than in the exclusively breastfed group (4/20), the full term gestational age (GA) group (17/20) than the pretenn GA group (3/20), and the normal birth weight group (15/20) than the low birth weight group (5/20). The median age of jaundice onset was 3.5 days (range lAO days), and the median duration of jaundice was 13.5 days (range 3-56 days). Conclusion The prevalence of UTI in infants aged 2􀁂8 weeks v.ith jaundice was 18.2%. More boys than girls had UTIs. The most common infecting microorganism found in our subjects was Escherichia coli. In daily medical practice, infants with prolonged jaundice of more than 2 weeks should be tested byurin alysis and urine cultures for the presence of UTIs. [Paediatr Indones. 2012;52:304-8].